Illocutionary Act Analisys Of The Main Character In Emancipation Movie And Its Contribution In Teaching Speaking - Maulana Yusuf Mahendra; Suwandi Suwandi; Fitri Yulianti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
In this research, the main focus is on illocutionary acts in the movie "Emancipation," analyzing the utterances of the main character, played by Will Smith as Peter. Five types of illocutionary acts, namely representatives, directives, commissive, expressive, and declarative, are examined and their frequencies are determined. The results reveal that representatives dominate the illocutionary acts, with 36% of the total utterances, followed by directives (23%), expressive (18%), commissive (14%), and declarative (9%). The research highlights the value of teaching illocutionary acts in speaking classes and suggests that using movies as teaching materials can be an engaging and effective approach. However, it is essential to choose appropriate instructional methods to ensure students' engagement and effective learning in the speaking skill. Ultimately, the study provides insights into how analyzing illocutionary acts in movies like "Emancipation" can contribute to enhancing students' speaking abilities.